2021
DOI: 10.1101/2021.01.08.425973
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trans-channel fluorescence learning improves high-content screening for Alzheimer’s disease therapeutics

Abstract: In microscopy-based drug screens, fluorescent markers carry critical information on how compounds affect different biological processes. However, practical considerations may hinder the use of certain fluorescent markers. Here, we present a deep learning method for overcoming this limitation. We accurately generated predicted fluorescent signals from other related markers, and validated this new machine learning (ML) method on two biologically distinct datasets. We used the ML method to improve the selection o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Transformation can take various forms, such as a direct copy 19 , partial channel drop 20 , or image masking 21 , with masked visual representation learning being a particularly popular method in natural image studies [22][23][24] . Furthermore, recent advances in cell segmentation algorithms have indicated that networks trained on generalized data can possess remarkable generalization ability [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Transformation can take various forms, such as a direct copy 19 , partial channel drop 20 , or image masking 21 , with masked visual representation learning being a particularly popular method in natural image studies [22][23][24] . Furthermore, recent advances in cell segmentation algorithms have indicated that networks trained on generalized data can possess remarkable generalization ability [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%